Korelasi dan Sidik Lintas Karakter Agronomi Padi Hibrida - Nita Kartina; Bayu Pramono Wibowo; Yuni Widyastuti; Indrastuti Apri Rumanti; . Satoto (Institut Pertanian Bogor, 2016)
Two approachment to increase yield productivity with new variety throught new plant type (NPT) concept and heterosis exploitation of hybrid rice. The research was to evaluated yield and yield component of 36 hybrid rice genotypes in preliminary yield trial at two locations. The experiment was conducted in the second season MT (II) 2013 at the Sukamandi experimentalstation, Subang, West JavaProvince and in Batang, Central Java Province by usingRandomized Complete Block Design (RCBD). The material used were36hybrid rice genotypes and four check varieties namely Hipa8, Hipa Jatim2,Ciherang, and Longping Optima. The results showed that grain yield had been effected by location, genotypes, and both interactions. There were two hybrid rice genotypes that give high yield potential than four check varieties, and one hybrid rice genotype significantly different from Longping Optima. Those hybrids were GMJ6/CRS519 (9.9 t/ha) and GMJ14/CRS757 (9.5 t/ha), and A1/CRS518 (6.2 t/ha). Based on path analysisnumber of productive tiller and number of total grain per panicle have direct effect to yield with path coefficient as 0.4028 and 0.2153. Length panicle and seed set also gave positif and significant direct effect to yield as 0.095 and 0.0956, so these characteristics could be used as selection criteria.